Quality of Service for Infant Massage Stimulation in Efforts to Prevent Stunting at the Regional Technical Implementation Unit of the Lere Community Health Center - Supit, Elisabeth; Daswati, Daswati; nuraisyah, nuraisyah (Jurnal Dialektika: Jurnal Ilmu Sosial, 2024)
The aim of this research is to describe the quality of Baduta Massage Stimulation Services in Efforts to Prevent Stunting in the Regional Technical Implementation Unit of the Lere Public Health Center. Usefulness of research in theoretical and practical aspects. By using the Qualitative Descriptive method and on a qualitative basis. With five informants. Quality of Baduta Massage Stimulation Services in Efforts to Prevent Stunting in the Regional Technical Implementation Unit of the Lere Community Health Center using the theory of Parasuraman, Zeithaml, and Berry (2013), in the form of five aspects, namely, Empathy, Reliability, Responsiveness), Tangibles (Physical Evidence), Assurance (Guarantee). The results of the research show that the quality of Baduta Massage Stimulation Services in Efforts to Prevent Stunting in the Regional Technical Implementation Unit of the Lere Community Health Center can be said to be optimal. This is shown from the Reliability aspect, that the services provided by health workers are timely; Daya considers that the Baduta Massage Stimulation service in Efforts to Prevent Stunting has been carried out quickly; Empathy, it is hoped that by applying empathy in public services, service officers can build better relationships with the public, increase their trust and satisfaction with the services provided; Physical Evidence, such as room facilities, complete equipment, adding and updating massage equipment that is more modern and in line with children’s stimulation needs; Guarantees: Strong guarantees in public services are one of the key factors in building public trust in the government or public institutions.